Adjuvant Treatment of Melanoma. (16th December 2012) - Moreno Nogueira, J. A.; Valero Arbizu, M.; Pérez Temprano, R.
Abstract : Melanomas represent 4% of all malignant tumors of the skin, yet account for 80% of deaths from skin cancer.While in the early stages patients can be successfully treated with surgical resection, metastatic melanoma prognosis is dismal. Several oncogenes have been identified in melanoma as BRAF, NRAS, c-Kit, and GNA11 GNAQ, each capable of activating MAPK pathway that increases cell proliferation and promotes angiogenesis, although NRAS and c-Kit also activate PI3 kinase pathway, including being more commonly BRAF activated oncogene. The treatment of choice for localised primary cutaneous melanoma is surgery plus lymphadenectomy if regional lymph nodes are involved. The justification for treatment in addition to surgery is based on the poor prognosis for high risk melanomas with a relapse index of 50–80%. Patients included in the high risk group should be assessed for adjuvant treatment with high doses of Interferon- α 2b, as it is the only treatment shown to significantly improve disease free and possibly global survival. In the future we will have to analyze all these therapeutic possibilities on specific targets, probably associated with chemotherapy and/or interferon in the adjuvant treatment, if we want to change the natural history of melanomas.